Targeting TFE3 Protects Against Lysosomal Malfunction-Induced Pyroptosis in Random Skin Flaps via ROS Elimination - Li, Jiafeng; Lou, Junsheng; Yu, Gaoxiang; Chen, Yijie; Chen, Ruiheng; Chen, Zhuliu; Wu, Chenyu; Ding, Jian; Xu, Yu; Jiang, Jingtao; Xu, Huazi; Zhu, Xuwei; et al. (Frontiers in Cell and Developmental Biology, 2021)
Increasing evidence indicates that pyroptosis, a new type of programmed cell death, may participate in random flap necrosis and play an important role. ROS-induced lysosome malfunction is an important inducement of pyroptosis. Transcription factor E3 (TFE3) exerts a decisive effect in oxidative metabolism and lysosomal homeostasis. We explored the effect of pyroptosis in random flap necrosis and discussed the effect of TFE3 in modulating pyroptosis. Histological analysis via hematoxylin-eosin staining, immunohistochemistry, general evaluation of flaps, evaluation of tissue edema, and laser Doppler blood ﬂow were employed to determine the survival of the skin flaps. Western blotting, immunofluorescence, and enzyme-linked immunosorbent assays were used to calculate the expressions of pyroptosis, oxidative stress, lysosome function and the AMPK-MCOLN1 signaling pathway. In cell experiments, HUEVC cells were utilized to ensure the relationship between TFE3, reactive oxygen species (ROS)-induced lysosome malfunction and cell pyroptosis. Our results indicate that pyroptosis exists in the random skin flap model and oxygen and glucose deprivation/reperfusion cell model. In addition, NLRP3-mediated pyroptosis leads to necrosis of the flaps. Moreover, we also found that ischemic flaps can augment the accumulation of ROS, thereby inducing lysosomal malfunction and finally initiating pyroptosis. Meanwhile, we observed that TFE3 levels are interrelated with ROS levels, and overexpression and low expression of TFE3 levels can respectively inhibit and promote ROS-induced lysosomal dysfunction and pyroptosis during in vivo and in vitro experiments. In conclusion, we found the activation of TFE3 in random flaps is partially regulated by the AMPK-MCOLN1 signal pathway. Taken together, TFE3 is a key regulator of ROS-induced pyroptosis in random skin flaps, and TFE3 may be a promising therapeutic target for improving random flap survival.